Regulatory consulting and banks’ financial reporting quality: evidence from the Dodd-Frank Act - Ballew, Hailey B.; Sheneman, Amy G. (Review of Accounting Studies, 2025)
Abstract The Dodd-Frank Act expands bank managers’ reporting requirements to federal agencies, particularly relating to banks’ financial losses should common market and macroeconomic shocks occur. To comply with this regulation, bank managers have engaged in consulting arrangements (referred to as regulatory consulting). We examine the financial reporting quality implications associated with hiring external auditors for these services. We find banks with auditor-provided regulatory consulting, relative to banks without, have higher financial reporting quality as measured by loan loss provision validity. Consistent with knowledge spillover benefits accruing to financial audit teams, we find more pronounced effects in the fourth versus interim quarters and more frequent income-reducing Y9-C restatements. We also find auditor responsiveness to PCAOB inspections improves the effectiveness of regulatory consulting. Overall, our results suggest regulatory consulting improves the audits of estimates in judgmental financial statement accounts, despite regulatory concerns that these services may impair auditor independence.